Modification of biochar with Fe3O4 and humic acid-salt for removal of mercury from aqueous solutions: a review. Issue 1 (31st December 2022) - Giwa, Abdulmoseen Segun; Ndungutse, Jean Maurice; Li, Yanfang; Mabi, Ahwei; Liu, Xinxin; Vakili, Mohammadtaghi; Memon, Abdul Gaffar; Ai, Luoyan; Chenfeng, Zhang; Sheng, Mingqiang
ABSTRACT: The application of magnetic biochar (MBC) has attracted significant attention due to its recyclability and adsorption capacity for Hg from aqueous solutions. However, its applicability is still inadequate, relying on poor selectivity. Some chemical substances could improve the sorption capacity of MBC. This review offers an advanced technological route to modify-MBC composition with significant adsorption volume toward Hg. Non-polluting humic acid-sodium salts (Ha-Na) were proposed to optimize Fe3O4-modified biochar (FBC), while the pyrolyzed substrate for the initial biochar (BC) production originated from any agricultural biomass material. The non-polluting Ha-Na can improve the FBC-specific surface area, the number and structure of pores, moderate the pH and adsorb Hg(II) from aqueous solutions. Further, the interaction of three simple projected equation mechanisms is proposed for BC, FBC, and Ha-Na. BC modified with the support of Fe3O4 and optimized by Ha-Na can be applied to improve Hg(II) adsorption, while insights and future investigations are suggested. Graphical abstract: uf0001